Petrographic characteristic of bauxites of the Koulore ore field - Lucien Toure; Alexey A Chausov; Alexander E Kotelnikov (RUDN Journal of Engineering Research, 2018)
As a result of studying geological structure of deposits located in the Koulore ore field, basic cross-section layers have been established: bedrock, transitional horizon and laterite cover. The laterite cover consists of the lower part presented by polymineral and kaolin clays and the top - the bauxite horizon - laterite cover itself, which generally contains hydroxides and oxides of iron and aluminum. The bauxite horizon has a zone structure: in the lower part of the bauxite horizon - zone of light bauxites, and in the top part of the bauxite horizon - zone of the red bauxites. As a result of microscopic study of various samples of residuum, several kinds of rocks which are characterized by similar structural and textural parameters have been identified. The rocks have been grouped by classes: gelified patterned bauxites on silt-rich mudstone, gelified bauxites on dolerites, gel-morphous bauxites with crystalloids on silt-rich mudstone, laterite bauxites (low-quality bauxites) on silt-rich mudstone, laterite bauxites (low-quality bauxites) on dolerites, ferruginous laterites - cuirass on silt-rich mudstone, ferruginous laterites of the top part of the transitional horizon on silt-rich mudstone. Lithological and genetic types of bauxites control the type and composition of aluminiferous minerals. Mineral composition of classical lateritic bauxites mainly contains gibbsite, goethite-alumogoethite, and hematite with less 1% of boehmite. Gel-morphous and gelified bauxites consist of gibbsite, boehmite, goethite-alumogoethite, hematite. Content of boehmite reaches 3% that is more than in classic lateritic bauxites. The composition of the alumogoethite depends not only on lithology of bauxites, but also on position in the residuum section.